2016
DOI: 10.1007/s40830-016-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges During Microstructural Analysis and Mechanical Testing of Small-Scale Pseudoelastic NiTi Structures

Abstract: Most investigations on NiTi-based shape memory alloys involve large-scale bulk material; knowledge about the martensitic transformation in small-scale NiTi structures is still limited. In this paper, we study the microstructures of thin NiTi layers and their mechanical properties, and we discuss typical challenges that arise when experiments are performed on small samples. A physical vapor deposition (PVD) process was used to deposit thin NiTi wires with a cross section of 15 9 15 lm 2 and dogbone-shaped sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…It is well known that NiTi thin films deposited on silicon substrates exhibit a random grain orientation fully in line with our observations as shown in Fig. 1a [14]. Such a randomly oriented microstructure is typically characterized by globular grains with grain sizes that are in the range of about 5-15 lm.…”
Section: Effect Of Graphene Layer On Preferential Niti Grain Orientationsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well known that NiTi thin films deposited on silicon substrates exhibit a random grain orientation fully in line with our observations as shown in Fig. 1a [14]. Such a randomly oriented microstructure is typically characterized by globular grains with grain sizes that are in the range of about 5-15 lm.…”
Section: Effect Of Graphene Layer On Preferential Niti Grain Orientationsupporting
confidence: 92%
“…We also found that a Cu interlayer (with a thickness of a few nanometers) can be used to adjust the adhesion between graphene and NiTi and to improve the adhesion conditions in general. Comparing our samples to recent results obtained from experiments using silicon substrates [8,14] together with Ni, Ti, and Cu interlayers, we did not expect to observe any influence on the NiTi grain orientation and grain size. However, after introducing the additional Cu layer between graphene and NiTi, we observed a quite different behavior, as discussed below.…”
Section: Effect Of Graphene Layer On Preferential Niti Grain Orientationsupporting
confidence: 71%
“…Second, a smooth film surface is essential, as only such a well-defined cut through the crystal allows distinguishing a martensitic microstructure from film morphology later on. Small scale mechanical testing also requires smooth surfaces to avoid crack formation in tensile tests [17] or adverse effects on nanoindentation measurements [18,19]. Both aspects can be examined best when the film is within the austenitic state at room temperature and therefore in the present study we focus on a film composition where the martensitic transformation occurs just below room temperature.…”
Section: Introductionmentioning
confidence: 99%